REALISTIC AND PSYCHOLOGICAL DEPICTION: EXAMPLE OF THE CHARACTERS OF THE NOVEL "GIRDOB" (Scientific journal of the Fergana State University, 2025)
Uktam Usmanov is one of the writers in Uzbek literature who is distinguished by his reflection of the complex contradictions of the human psyche and society. He is the author of several short stories and collections of stories and the novel "Girdob". His novel "Girdob" tells about complex problems in society, human contradictions, internal experiences and social changes. In the novel, the author demonstrated his artistic skills by deeply analyzing the inner world of various characters and realistically depicting their characters. This article analyzes the images of Aziz Kasimov, Saltanat, Yuldosh, Muhiddin Jabborovich and Rasul Olloyorovich in the novel "Girdob" and reveals Uktam Usmanov's style of creating images.